Russian companies forming information and communication technology groundworks - P. V. Tereliansky (Управление)
The object of the research is the data of annual reports on the volume of sales of products of five hundred leading Russian companies, collected and presented by the national business analytical resource “Expert Online”  together with the magazine “Russian reporter” and the media holding “RosBusinessConsulting”. The author analyses the volume of sales of Russian companies, whose activities can be attributed to the field of information and telecommunications technologies. Elements of the financial statements of companies that are  engaged in the creation, promotion and analysis of media content have been also considered. The analysis showed that the total volume of sales of twenty-two companies belonging to the sectors “Information  technology”, “Telecommunications”, “Media and Internet”, amounted to 2 615 billion rubles, which is compared with the volume of sales of 11 883 billion rubles of the first twenty-two leading domestic companies (related to the resource sector) is only 22 percent. Consequently, less than a quarter of the total sales of goods and services in the Russian economy are sold by companies whose activities are related to the formation of information and communication reserves. Such an assessment can only be made indirectly on the basis of dimensionless values, such as calculating the percentage of sales volumes of IT companies and companies included in the considered ratings in the first positions. For reference, the author provides financial indicators in rubles and dollars as of December 16, 2019, according to the Central Bank of the Russian Federation.The article continues the author’s research presented in the paper “The process of transformation of the real export-oriented economy of Russia into a digital one” (in the journal Upravlenie, 2018, no. 4) and in the report “The process of digital transformation of the Russian economy”, at the II All Russian scientific and practical  conference with international participation “Trends in the development of the Internet and digital economy” (Simferopol-Alushta, May 30 – June 1, 2019).